Acoustic resonance coupling for directional wave control: from angle-dependent absorption to asymmetric transmission - Taehwa Lee; Hideo Iizuka (New Journal of Physics, 2019)
We investigate acoustic wave coupling between two resonators of very different intrinsic losses, e.g. lossy and lossless resonators as an extreme case. We find that the resonator pair placed on a reflector exhibits angle-dependent absorption, showing an order of magnitude difference for opposite angles of incidence. The results obtained from a harmonic oscillator model show excellent agreement with numerical results. Moreover, our analytical model explicitly describes the contribution of radiation leakage and coupling to the angle-dependent absorption, enabling one to design a simple resonant structure demonstrating asymmetrical transmission.